Application of ethanol extract od propolis (EEP) in nutrition and development of coffee seedlings - Pereira, Cassiano Spaziani; Farias, Fausto Lima; Godoi, Cícero Aparecido (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the effect of ethanol extract of propolis (EEP) in nutrition and leaf developmentof seedlingsof Coffea arabica cv. Catuaí vermelho. The design was randomized blocks with five replications and ten plants each. The experiment was a factorial scheme 4 x 6. The first factor consisted of four ethanolic extracts of propolis, with differents percentages in the composition of the propolis (1,4, 7 and 10% of raw propolis with ethanol and the remaining 92%). The second factor was the dilution of the EEP, 0, 0.5, 1.0, 1.5, 2.0 and 2.5% in water. For the evaluation of the nutrient levels took into account only the concentrations of all treatments with EEP made with 10% propolis extract. It was concluded that: The ethanol extract of propolis (EEP) made with 4% of crude propolis promotes increased of the leaf area expanded; the EEP has not changed the K, P, S, Mg, Fe, Cu and B, in coffee seedlings, the EEP change the concentration of N, Mn, Zn and Ca, the dry masses of roots, shoots and increased with total the EEP.